PENGARUH FOMO (FEAR OF MISSING OUT) TERHADAP MOTIVASI BELAJAR SISWA DI ERA DIGITAL - Meutia Najwa Prabarani; Mahmuddah Dewi Edmawati (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2026)
The research approach used in this study is Qualitative with a phenomenological design to understand students' subjective experiences related to the FoMO (Fear of Missing Out) phenomenon in the digital era and how these experiences influence their learning motivation in the digital environment. The author aims to describe students' attitudes and experiences in dealing with FoMO in the digital era and analyze the influence of FoMO on students' learning motivation. Data collection was carried out through observation, open interviews, and documentation. Observations were used to see students' learning behavior in their daily lives, open interviews to explore students' subjective experiences related to FoMO, and documentation to complement and strengthen the research data. The data analysis technique used triangulation, namely comparing and linking the results of observations, interviews, and documentation to ensure the validity and depth of meaning of the data.